(untitled) (Al-Qamar, 2020)
Arabic is one of the richest human languages, and it has many linguistic characteristics. Arabs have methods for strengthening, emphasizing and decorating speech, and expressions that denote eloquence, and indicate eloquence and ingenuity. It contains linguistic phenomena that are lacking in other languages. Among these phenomena is one of the methods of the Arabs in their speech, and what has affected them. Arab scholars had efforts in studying the Following (al-Ittibāʻ) - out of their concern for Arabic and their eagerness to discuss its issues and phenomena, and their positions on the topic varied, and their views and opinions differed on it. This paper discusses the reality of this phenomenon in the Arabic language and the opinions of Arab linguists about it.